Zibibbo Grape Seeds' Polyphenolic Profile: Effects on Bone Turnover and Metabolism - Mariagiovanna Settino; Samantha Maurotti; Luca Tirinato; Simona Greco; Anna Rita Coppoletta; Antonio Cardamone; Vincenzo Musolino; Tiziana Montalcini; Arturo Pujia; Rosario Mare (MDPI AG, 2024)
Background: The consumption of seeds as food has become increasingly common due to their numerous health benefits. Among these, the seeds of the Zibibbo grape from Pantelleria, a native species of southern Italy, remain largely unexplored and are usually considered waste material from viticulture. Nevertheless, Zibibbo grape seeds may offer health benefits, particularly for the elderly and people with metabolic disorders, due to their potential content of beneficial compounds such as polyphenols. Methods: The Zibibbo grape seeds extract (ZSE) was characterized using UV-visible spectrophotometry and HPLC chromatography. The antioxidant activity of ZSE was measured by different colorimetric assays and Electronic Paramagnetic Resonance (EPR). Additionally, specific in vitro tests were conducted on human osteoblast cell lines (Saos-2 and MG63) aiming to evaluate the ZSE's effects on bone turnover and metabolism. Western blotting was used to assess the impact on specific proteins and pathways related to bone health. Results: The ZSE contained almost ~3 mg/mL of carbohydrates and phenolic compounds, including rutin (~6.4 ppm) and hesperidin (~44.6 ppm). The extracts exhibited an antioxidant activity greater than 90% across all tests performed. Moreover, the Zibibbo seed extracts exerted a significant proliferative effect on the Saos-2 cell human osteoblast-like cell line, also modulating the phosphorylation of specific kinases involved in cell health and metabolism. Conclusions: Zibibbo grape seeds are rich in phenolic compounds, especially flavonoids with strong antioxidant and free radical scavenging properties. ZSE demonstrated beneficial effects on bone metabolism and osteoblast proliferation, suggesting potential for counteracting osteodegenerative conditions like osteoporosis. If confirmed through further studies, Zibibbo grape seed phenolic compounds could serve as an adjunctive therapy for osteoporosis, helping to slow aging and bone degeneration.